The integration strategy and effect evaluation of art teaching and mental health counseling in preschool education - He, Fanlun (International Journal of Social Sciences and Public Administration, 2024)
As the foundation period of primary education, preschool education is an indispensable part of the national education system, which plays a significant role in the physical, psychological, and physiological aspects of individuals. As an essential introductory course of preschool education, art education not only bears the responsibility of aesthetic education but also plays an essential role in the development of mental health because of its disciplinary characteristics. In this paper, the control group will receive traditional art education and mental health counseling separately, while the experimental group will be provided with a holistic art education program and integrated counseling for mental well-being. The experimental results will have specific practical significance for improving children’s art education and promoting children’s mental health development.